2020
DOI: 10.3390/ijms21072564
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Polyphenols and Neuromodulation: Molecular Mechanisms in Neurodegeneration

Abstract: The interest in dietary polyphenols in recent years has greatly increased due to their antioxidant bioactivity with preventive properties against chronic diseases. Polyphenols, by modulating different cellular functions, play an important role in neuroprotection and are able to neutralize the effects of oxidative stress, inflammation, and apoptosis. Interestingly, all these mechanisms are involved in neurodegeneration. Although polyphenols display differences in their effectiveness due to interindividual varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 145 publications
1
64
0
Order By: Relevance
“…Consistent findings from several studies confirm that these natural compounds can induce a positive effect on several cognitive processes, specifically executive function, attention, working memory, and processing speed [13]. Moreover, polyphenols can also exert neuroprotective functions due to their effectiveness against oxidative stress and inflammation as well as their capacity to modulate prosurvival or antiapoptotic Nutrients 2020, 12, 3691 2 of 14 signaling pathways [14]. Interestingly, better beneficial effects of polyphenols on brain plasticity biomarkers and on different cognitive functions have been found in young and middle-aged adults than in elderly [12,15], suggesting that young people can be an attractive population target to prevent onset of age-related diseases and cognitive decline.…”
Section: Introductionmentioning
confidence: 64%
“…Consistent findings from several studies confirm that these natural compounds can induce a positive effect on several cognitive processes, specifically executive function, attention, working memory, and processing speed [13]. Moreover, polyphenols can also exert neuroprotective functions due to their effectiveness against oxidative stress and inflammation as well as their capacity to modulate prosurvival or antiapoptotic Nutrients 2020, 12, 3691 2 of 14 signaling pathways [14]. Interestingly, better beneficial effects of polyphenols on brain plasticity biomarkers and on different cognitive functions have been found in young and middle-aged adults than in elderly [12,15], suggesting that young people can be an attractive population target to prevent onset of age-related diseases and cognitive decline.…”
Section: Introductionmentioning
confidence: 64%
“…Interestingly, luteolin restored the growth of vps13 cells regardless of the presence of multiple copies of FET4 ; thus, the effect of these two factors was not additive, suggesting that they act on the same process. Possible mechanisms of flavonoids and iron action involve binding to specific proteins, affecting metabolic or signaling pathways, or changing gene expression to induce a protective response in cells against SDS stress [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the continuous improvement of medical standards, the average life span of humans has been significantly extended, but correspondingly, diseases related to brain aging caused by an aging population have also increased significantly, such as cognitive and neurodegenerative diseases [ 109 ]. Neurodegenerative diseases, characterized by the progressive loss of functions of a large number of neurons and neural stem cells, leading to sensory deficits and cognitive impairments, are a type of progressive, disabling and severely fatal complex disease [ 110 ]. Studies have found that all neurodegenerative diseases share a common cellular and molecular mechanism, that is, oxidative stress accumulation, inflammation, protein misfolding and aggregation, neurotoxicity, etc.…”
Section: Bioactivities Of Polyphenolsmentioning
confidence: 99%